2016
DOI: 10.3346/jkms.2016.31.11.1711
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Adverse Events after Conversion from Twice-Daily to Once-Daily Tacrolimus in Stable Liver Transplantation Patients

Abstract: Despite the therapeutic equivalence between twice-daily and once-daily tacrolimus, patient safety after conversion is still a concern. We reviewed 218 liver transplantation (LT) patients who converted twice-daily to once-daily tacrolimus between May 2011 and January 2014. Thirty (13.8%) patients had adverse events after conversion, with a liver function test (LFT) abnormality being the most common adverse event (n = 17). Despite the decrease in serum tacrolimus of > 30% after conversion, none of the patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 21 publications
5
12
0
Order By: Relevance
“…Up to 25% of the patients required a tacrolimus dose increase after the conversion. These findings are consistent with the results of other oncedaily tacrolimus conversion studies in LT patients, [9][10][11]16 A 15-20% increase in the daily dose of tacrolimus has been suggested in order to achieve the same target trough level of the drug following the conversion. 19 CYP3A5 expression was shown to influence tacrolimus exposure, with the exposure in CYP3A5 expressors receiving either twice-daily tacrolimus or once-daily tacrolimus being lower than in the non-expressors.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Up to 25% of the patients required a tacrolimus dose increase after the conversion. These findings are consistent with the results of other oncedaily tacrolimus conversion studies in LT patients, [9][10][11]16 A 15-20% increase in the daily dose of tacrolimus has been suggested in order to achieve the same target trough level of the drug following the conversion. 19 CYP3A5 expression was shown to influence tacrolimus exposure, with the exposure in CYP3A5 expressors receiving either twice-daily tacrolimus or once-daily tacrolimus being lower than in the non-expressors.…”
Section: Discussionsupporting
confidence: 90%
“…3,10,[14][15][16] Several previous studies demonstrated that liver dysfunction is the most common adverse event after converting from twice-daily to once-daily tacrolimus. 11 In our present study, the incidence of liver dysfunction in stable liver transplant recipients converted to once-daily extended-release tacrolimus was higher in the CYP3A5 expressor group than in the non-expressor group. However, the between group difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Patient selection and post‐LT immunosuppressive details have been previously described . Usage of mammalian target of rapamycin inhibitor (mTORi) was considered for patients with far advanced HCC, defined as HCC larger than 10 cm or more than 10 in number, or with macrovascular invasion, 1 month after LT .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that in stable patients after LT, conversion from twice-daily to once-daily tacrolimus was well-tolerated, safe, and convenient [ 10 , 11 ]. However, despite the similar pharmacokinetics of the twice-daily and once-daily tacrolimus, some patients experienced adverse events, including liver dysfunction, after the conversion [ 12 ].…”
Section: Introductionmentioning
confidence: 99%